2012
DOI: 10.1002/lary.23424
|View full text |Cite
|
Sign up to set email alerts
|

Readability assessment of internet‐based patient education materials related to facial fractures

Abstract: IPEMs related to FFs are written above the recommended 6th-grade reading level. Consequently, this information would be difficult to understand by the average US patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
3

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 37 publications
4
51
0
3
Order By: Relevance
“…Our findings are congruent with readability assessments in the literature. IPEMs across various sources are written above the recommended sixth-grade reading level (10)(11)(12)(13)(14). For example, Tian et al (26) demonstrated similar results with IPEMs pertaining to colon cancer screening.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our findings are congruent with readability assessments in the literature. IPEMs across various sources are written above the recommended sixth-grade reading level (10)(11)(12)(13)(14). For example, Tian et al (26) demonstrated similar results with IPEMs pertaining to colon cancer screening.…”
Section: Discussionmentioning
confidence: 72%
“…The US Department of Health and Human Services (USDHHS), American Medical Association, and the National Institutes of Health recommend that IPEMs be written at or below the sixth-grade level (6). Readability analyses have been established to evaluate IPEMs available to patients (1,6 of medicine to calculate readability of IPEMs available to their patient population (10)(11)(12). Readability assessments have recently been published in the radiology literature (13,14).…”
mentioning
confidence: 99%
“…Yapılan diğer çalışmalarda da eğitim materyallerinin okunabilirlik düzeyi yüksek olarak bulunmuştur [9,[23][24][25][26][27]. Literatürde web tabanlı emzirme ile ilgili sadece bir çalışmaya rastlanmıştır.…”
Section: Verilerin Toplanması 1-web Sitelerinin Tasarımıunclassified
“…A number of studies [7][8][9][10][24][25][26][27][28][29] have shown that PEMs across numerous fields of medicine are written well above the AMA recommended 6 th grade reading level. However, this benchmark of a 6 th grade reading level may be misleading.…”
Section: Limitations Of the Studymentioning
confidence: 99%